Effect Of Water Hyacinth (Eichhornia crassipes) Fermentation Using a Cow Rumen Fluid As Fish Meal of Osphronemus gouramy Lac Fingerling - Puji Haryadi; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted for 56 days from August to October 2015. The aim of this research was to find out respons of Osphronemus gouramy Lac fingerling on water hyacinth fermentations. The methods used in this study was an experimental method and RAL one factor with stocking density of 5 treatments. The fish used in this research with size of 5-7 cm in length and 3,3 – 5,6 g in weight. Fish were reared in 1 m3 in keramba with stocking density of 20/keramba. Feeding trials were replacing with soybean meal with water hyacinth fermentation applied to 0, 10, 20, 30 and 40% for 30% protein content.Result showed that fermentation of water hyacinth have significant effect (P<0,05) on growth, feed efficiency, and protein retentions. Replacement 10% of water hyacinth fermentation is the best respons, produce the highest growth 2.21%, feed efficiency 21.01%, protein retention 20.89%, and 52.38% feed digestion respectively.Key word: Osphronemus gouramy, Water Hyacinth,Fermentation, Rumen Fluid